Anticoagulated patient management in primary care service - Marco Antonio Zapata Sampedro; Sandra García Fuente; Ana Jiménez Gil (Fundación para el Desarrollo de la Enfermería, 2008)
Out-patients undergoing anticoagulant treatment are attended by nursing staff, working with doctors.To be able to provide adequate medical care, nurses must have the minimum knowledge and skills needed to work with the programme described in this article. These include basic and specific knowledge of anticoagulation. The correct functioning of the service will help provide an optimum control of the INR (International Normalized Ratio) and reduce the complications of bleeding, both of which are the main objectives of the nursing care of these patients.